(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
Monitoring on the panicle initiation, flowering, fruiting and seedling characteristics of Corypha taliera has been carried out. Biochemical composition of fresh and dry flowers together with the pericarp of the fruits have been analysed. Fresh flowers, fruits, seeds, and pericarp and testa weighed 13.75 mg/flower, 19.46 g/fruit, 6.47 g/seed, 12.89 g/pericarp and testa, respectively. The length of fruits and seeds were c 3.34 cm and c 2.33 cm, respectively while the breadth of the same were 3.14 cm and 1.94 cm, respectively. The protein content of fresh flower and pericarp were 12.78 and 14.70%. High energy content 345.97 Kcal was recorded in the pericarp and testa of the fruit. The first sown seeds were germinated in latterite clay soil between January and February and took approximately 30-48 days. Keywords: Corypha taliera; biochemical composition; flowers; fruits; pericarp. DOI: 10.3329/bjpt.v17i1.5393 Bangladesh J. Plant Taxon. 17(1): 79-86, 2010 (June)